Hemodynamic effects of sildenafil citrate (Viagra) on segmental branches of bilateral renal arteries - Ardicoglu, Arslan; Kocakoc, Ercan; Yuzgec, Veysel; Bozgeyik, Zulkif; Canatan, Halit; Kiris, Adem (My University, 2005)
Introduction: Erectile dysfunction (ED) is one of the most encountered male health problem and sildenafil citrate is used worlwide for treatment of ED. Aim of the present study was to determine and evaluate hemodynamic effects of sildenafil citrate on segmental branches of bilateral renal arteries of cases with ED. Patients and methods: Total of 35 male patients aging between 34 and 56 years were recruited into study. Patients were evaluated with renal color Doppler sonography (CDS) before and after (45-75 min) peroral sildenafil citrate (50 mg) administration. Peak sistolic flow rate (Vmax), end diastolic flow rate (Vmin), resistive index (RI) and pulsatility index (PI) of renal artery segmental branches were determined before and after sildenafil citrate administration. Results: Vmin measured at right lower segment was significantly reduced after sildenafil administration (p=0.030). Accordingly mean RI and PI of right lower segment of renal artery slightly increased after drug administration (p=0.007 and p=0.012, respectively). The measurements on other segments had no significant change after sildenafil treatment when compared to baseline values. On this single dose administration no side effect was recorded. Conclusion: Findings of the present study demonstrated that peroral sildenafil citrate usage had slight effects on hemodynamic parameters of lower segmental branch of right renal artery. This result could not be interpreted as robust evidence for hemodynamic changes of renal arteries associated with slidenafil usage nevertheless warrants more comprehensive research with larger number of patients. © Springer 2005.
Keywords: Color Doppler ultrasonography; Renal artery; Sildenafil citrate